Noteworthy records of aphyllophoroid fungi in Finland (Basidiomycota) - Kunttu, Panu; Pennanen, Jorma; Kekki, Tapio; Kulju, Matti; Suominen, Mai (Acta Mycologica, 2014)
We present new records of noteworthy aphyllophoroid fungi, mainly polypores and corticioids in Finland. The following 19 rare or infrequently collected species are presented with notes on their substrates: Amylocorticium subsulphureum, Antrodiella parasitica, Ceraceomyces sulphurinus, Clavaria atroumbrina, Clavaria rosea, Gloeophyllum carbonarium, Hyphodontia flavipora, Junghuhnia fimbriatella, Lindtneria chordulata, Odonticium septocystidia, Peniophorella guttulifera, Perenniporia tenuis, Postia immitis, Repetobasidium vile, Resinicium pinicola, Sidera vulgaris, Tomentella coerulea, Trechispora laevis and Xylodon pruni. We also list 41 aphyllophoroid fungi as new to some sections of the boreal vegetation zone in Finland.